2014
DOI: 10.2337/dc14-1395
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Metformin: Safety Considerations in the Decision-Making Process for Selecting a Second Medication for Type 2 Diabetes Management

Abstract: The trend toward personalized management of diabetes has focused attention on the differences among available pharmacological agents in terms of mechanisms of action, efficacy, and, most important, safety. Clinicians must select from these features to develop individualized therapy regimens. In June 2013, a nine-member Diabetes Care Editors’ Expert Forum convened to review safety evidence for six major diabetes drug classes: insulin, sulfonylureas (SUs), thiazolidinediones (TZDs), glucagon-like peptide-1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 130 publications
0
48
1
4
Order By: Relevance
“…4,7,8 Até o momento, os estudos clí-nicos randomizados foram incapazes de demonstrar efeito desfavorável das sulfonilureias sobre o risco cardiovascular. 8,9 A dificuldade desse tipo de estudo em mostrar dados potenciais de medicamentos é comum, uma vez que, para isso, é necessário grande número de pacientes e longo tempo de seguimento.…”
Section: Sulfonilureia E Risco Cardiovascularunclassified
See 1 more Smart Citation
“…4,7,8 Até o momento, os estudos clí-nicos randomizados foram incapazes de demonstrar efeito desfavorável das sulfonilureias sobre o risco cardiovascular. 8,9 A dificuldade desse tipo de estudo em mostrar dados potenciais de medicamentos é comum, uma vez que, para isso, é necessário grande número de pacientes e longo tempo de seguimento.…”
Section: Sulfonilureia E Risco Cardiovascularunclassified
“…A disponibilidade dessas novas opções para o tratamento do diabetes em questão tornou a escolha de quais medicamentos usar em determinado paciente, tarefa cada vez mais complexa. 4 As principais diretrizes de tratamento do diabetes melito tipo 2 recomendam a metformina como monoterapia inicial em doentes que a tolerem, dada a sua eficácia em controlar a glicemia, ao seu baixo custo, à sua segurança e ao seu potencial de redução do risco cardiovascular. 1,5,6 Em razão da natureza progressiva da doença, é frequente, porém, a necessidade de adição de outros medicamentos para obtenção de controle glicêmico e, nessa etapa do tratamento, várias opções estão disponíveis, e a escolha é direcionada por características individuais do paciente e não há recomendação geral sobre a preferência de uma classe de medicamentos em relação a outra.…”
Section: Introductionunclassified
“…A large proportion of weight gain attributed to the initiation of insulin therapy can be avoided with simple lifestyle reinforcement measurements. In consideration of lifestyle modification or any other longterm treatment of type 2 diabetes, the importance of teamwork and patient empowerment cannot be underestimated (18,19). Teamwork includes a multidisciplinary team of nurses, dietitians, social workers, medical psychologists, and the treating physician.…”
Section: Medical Guidelines For the Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…First, individualization of the stringency by which glycemic control targets are set (1,(16)(17)(18)(19) has left many open questions regarding the best glycemic target for a given patient (20)(21)(22). While the ADA/EASD Position Statement (1,2) supports a target HbA 1c of ,7% for most patients, it recommends a more stringent target (HbA 1c 6.0-6.5%) for select patients, as long as it can be achieved without increased risk of hypoglycemia or other prominent side effects.…”
Section: Medical Guidelines For the Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…A similar conclusion was reported in a recent published consensus report from Diabetes Care that suggested that "the ideal antihyperglycemic agent would be easy to administer, unlikely to cause symptomatic side effects that pose barriers to adherence, inexpensive, reliably efficacious, and safe. By such standards, it can be argued that the remaining modern SUs do well (although they do leave some clinical needs unmet)" (25). …”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 99%